Electroni Structure in crystalline system of Ge, GaP and SiC - Cabrera, César (2018)
Be study the electronic structure of Ge and of the compounds GaP and SiC, we utilized a local density potential (LDA) and the method (LMTO) we present the calulated energy band, band-gaps, the density occupied states DOS, the total energy of crystalline system. There is good agreement between the calculated electronic properties and experimental results.